2016
DOI: 10.1039/c5sc02739j
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective palladium-catalyzed deprotonative arylation/[1,2]-Wittig rearrangement of pyridylmethyl ethers

Abstract: Control of chemoselectivity is one of the most challenging problems facing chemists and is particularly important in the synthesis of bioactive compounds and medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…Subsequent studies by the same group have identified (again) CPME as the solvent of choice for the first chemoselective tandem C(sp 3 )−H arylation/[1,2]‐Wittig rearrangement of pyridylmethyl ethers under Pd‐catalysis conditions (Scheme ) . Optimization studies have revealed the critical role played by the base/solvent/temperature and have thus allowed the design of a divergent synthesis of tertiary and quaternary adducts.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies by the same group have identified (again) CPME as the solvent of choice for the first chemoselective tandem C(sp 3 )−H arylation/[1,2]‐Wittig rearrangement of pyridylmethyl ethers under Pd‐catalysis conditions (Scheme ) . Optimization studies have revealed the critical role played by the base/solvent/temperature and have thus allowed the design of a divergent synthesis of tertiary and quaternary adducts.…”
Section: Synthetic Applicationsmentioning
confidence: 99%
“…Subsequents tudies by the same group have identified (again) CPME as the solvent of choice for the first chemoselective tandem C(sp 3 )ÀHa rylation/[1,2]-Wittig rearrangemento fp yridylmethyl ethers under Pd-catalysis conditions (Scheme 18). [36] Optimization studies have revealed the critical role playedb yt he base/solvent/temperature andh ave thus allowed the design of ad ivergent synthesis of tertiary and quaternary adducts. Accordingly,t he tandem process becomes highly selective by selecting the LiN(TMS) 2 /CPME/45 8Ct riad, whereas the corresponding sodium base in DME at 23 8Cf urnishes the simplea rylated product.…”
Section: Use Of Cpme In Transition-metal-catalyzed Chemistrymentioning
confidence: 99%
“…We are interested in alternative strategies to selectively arylate weakly acidic (p K a 25–35) benzylic C–H bonds of arenes and heteroarenes. Our strategy relies on reversible deprotonation of the C–H bonds of the benzylic pronucleophile in the presence of the catalyst, which then arylates the substrate. A limitation of this approach is that some benzylic C–H bonds, such as those in toluene, have such high p K a values (∼43 for toluene in DMSO) that appreciable deprotonation in the presence of a transition metal catalyst is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions involve a weakly acidic C–H of the substrate (pronucleophile) that is reversibly deprotonated under the reaction conditions. Subsequently, the nucleophile undergoes catalyst promoted arylation 33 34 35 36 or vinylation 37 . This method has been particularly successful with the generation of triarylmethanes 38 39 40 .…”
Section: Discussionmentioning
confidence: 99%